2021
DOI: 10.1111/bjd.19819
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre study of naevus‐associated melanoma vs. de novo melanoma, tumour thickness and body site differences*

Abstract: Background Whether melanoma in histological contiguity with a naevus [naevusassociated melanoma (NAM)] is distinctly different from melanoma arising de novo remains unclear. Objectives To determine whether the characteristics of de novo melanoma differ from NAM and are not due to naevus obliteration in thicker tumours. Methods We conducted a multicentre retrospective study of de novo melanoma and NAM in seven referral centres in Europe, Australia and the USA between 2006 and 2015. Results In a total of 9474 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 38 publications
(90 reference statements)
2
32
0
Order By: Relevance
“…Although the relationship between NAMs and DNMs has been carefully studied in the past ( Cymerman et al., 2016 ; Dessinioti et al., 2021 ; Lin et al., 2015 ; Martin-Gorgojo et al., 2018 ; Pampena et al., 2017 ; Reiter et al., 2021 ; Sheen et al., 2017 ), the unsupervised clustering suggests that NAMs are more similar to each other across all CP features than DNMs. In other words, NAMs (e.g., TC1–2) tend to be less mitogenic, less ulcerative, and less thick than DNMs (TC3–5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the relationship between NAMs and DNMs has been carefully studied in the past ( Cymerman et al., 2016 ; Dessinioti et al., 2021 ; Lin et al., 2015 ; Martin-Gorgojo et al., 2018 ; Pampena et al., 2017 ; Reiter et al., 2021 ; Sheen et al., 2017 ), the unsupervised clustering suggests that NAMs are more similar to each other across all CP features than DNMs. In other words, NAMs (e.g., TC1–2) tend to be less mitogenic, less ulcerative, and less thick than DNMs (TC3–5).…”
Section: Discussionmentioning
confidence: 99%
“…(2015) reported significant associations in ulceration status, age, pathologic subtype, and truncal site in NAMs; however, their study exclusively selected patients undergoing sentinel lymph node biopsy. Furthermore, investigators have shown a central anatomic site (e.g., head, neck, and truncal areas) predisposition for DNMs and increased likelihood of nodular subtype DNMs that are truncally located ( Dessinioti et al., 2021 ). Pandeya et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the growing literature on the role of phenotypic characteristics in melanoma development, [6][7][8] the study of pathway-specific PRSs and melanoma risk is a recent development. PRSs are increasingly being applied to predict the risks of several complex disorders.…”
mentioning
confidence: 99%